General self-efficacy, pre-competitive anxiety and flow feeling in handball team players from Costa Rica’s nactional team - Gutiérrez Vargas, Juan Carlos (2013)
The purpose of this study was to describe and analyze the relationship between self-efficacy, pre-competitive anxiety and flow feeling in male and female handball team players from the  Costa Rica national teams. Participants were 28 players (14 male and 14 female) from both teams. The scales of general self-efficacy, flow feeling and competitive anxiety were used to collect data. The average score in relation to self-efficacy was high (> 8.40). Regarding flow sensation, the average scores were range from 3.41 (autotelic experience)  to 5,78 (control sense). Somatic anxiety was the lowest in men = 1.59 and women female = 1.98, and self-confidence was the highest score in men = 2.99 and women = 2.70 respectively.  No significant changes were observed throughout the game in relation to the flow feeling. The anxiety reported by men was significantly lower than women, and the self-confidence levels were higher in men than in women. No significant correlation was found between self efficacy and sense of flow.  Somatic anxiety showed significant correlations with some dimensions of the flow feeling. In conclusion, these data showed that there is a need to incorporate psychological interventions to ensure that athletes can reach optimal psychophysical states in order to perform better.